2 - Bilan d’une décennie de la coopération économique Arabo-Africaine: Quelques point de repères analytiques - Bernard FOUNOU-TCHUIGOUA; Charbel ZAROUR (Africa Development, 1986)
This paper is a critical evaluation of Afro-Arab regional cooperation since the start of Arab aid based on the oil revenue. The present stage of the Afro-Arab 'cooperation was begun in 1974 with the creation of BADEA and with the first Afro-Arab economic summit held in 1977 in Cairo. The objective of this summit was to formulate a regional economic cooperation between Arab and African States. The issues involved were the position of these States vis-a-vis the Center within the framework of NWEO and the development of horizontal cooperation in such areas as trade, finance, currency and technological, scientific and cultural exchanges. However, the paper argues that in actual fact, Arab public aid was the major issue discussed. Yet this aid is neither significant nor unrelated to financial aid from the "North". It is rather complementary to the latter. Among the factors which produced such a result, special attention is given to structural distortions which are necessarily generated by the transformation of this oil revenue into human and physical means of accumution. Therefore, contrary to widely held assumptions, Afro-Arab cooperation did not facilitate autocentric accumulation which would have facilitated the dilinking of these states from the Center. This aid was only a way to adjust to the Changing World Capitalist System.